L'URSS dentro e fuori La narrazione italiana del mondo sovietico - Traini, Cheti (Biblioteca di Studi di Filologia Moderna, 2022)
From the 1920s onwards, the Soviet Union became a favourite destination for Italian writers, travellers who took it upon themselves to interpret and present the new Soviet world to Italian readers by sending articles to newspapers and magazines, most of which were later published as monographs. The present study aims to investigate the reasons that drove so many intellectuals to visit Russia and the Soviet territories after the October. Through references to historical and political ideologies that may have influenced the writers' interpretations, the reconstruction of travel conditions and individual approaches to Soviet life, the study focuses on Italian intellectuals' views on the USSR and the particular value that the reportages had in the construction of the image of the Soviet world in the Italian reality.